Academic workload and lifestyle predict emotional well-being among university students in the United Arab Emirates: A cross-sectional study - Munawar Farooq; Uffaira Hafeez; Amir Ahmad; Susan Waller; Gabriel Andrade; Arif Alper Cevik; Syed Fahad Javaid (PLoS ONE, 2026)
Background Stress is a prevalent issue among university students and is linked to adverse academic and emotional outcomes. While research emphasizes the roles of resilience, personality traits, and psychosocial factors, most studies are drawn from North American and European contexts. Objectives This is the first study of its kind in the United Arab Emirates (UAE) exploring the relationship between perceived stress, resilience, and personality traits among university students, offering insights into region-specific influences on emotional well-being. Methods An online cross-sectional survey was conducted among 168 students from two colleges at the United Arab Emirates University (79% College of Medicine and Health Sciences, 21% College of Information Technology; 72% female). Data were analyzed using descriptive statistics and regression models in R version 4.2.0. Personality traits were assessed using the Ten-Item Personality Inventory, perceived stress was measured with the Perceived Stress Scale, and resilience was evaluated with the Brief Resilience Scale. Results The median perceived stress score was 22 (IQR: 17–28), and 30% reported high stress. Multivariable analysis showed that heavier academic workload, financial difficulties, lack of social support, lower physical activity, and poorer academic performance significantly predicted higher perceived stress, whereas resilience and emotional stability were protective. Conclusion University students’ perceived stress is closely associated with modifiable factors, including academic workload, social support, resilience, and physical activity. Targeted interventions, such as resilience training, promoting physical activity, optimizing academic schedules, and strengthening support services, are vital to reducing perceived stress and enhancing student well-being.